Multilingual Landscapes : 4th Exhibition of the Soros Center for Contemporary Arts - Lithuania. - Jurenaite, Raminta (Vilnius : Soros Center for Contemporary Arts, 1997)
Bednarski, Krzysztof ; Bozis, Eriks ; Csorgo, Attila ; Kafka, Ivan ; Kuprijanov, Vladimir ; Mihailov, Boris ; Petercol, Goran ; Rama, Edwin ; Sumkovski, Jovan ; Toomik, Jaan ; Urbonas, Gediminas ; Zaltauskas, Vytautas
biografie
Multilingual Landscapes : 4th Exhibition of the Soros Center for Contemporary Arts - Lithuania, Contemporary Art Centre, Vilnius, November 22, 1996 - January 5, 1997
Engels & Litouws
kunstcatalogus